2019
DOI: 10.2196/15847
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Research Priorities of Parents Who Have Children With Down Syndrome, Cleft Lip With or Without Cleft Palate, Congenital Heart Defects, or Spina Bifida Using ConnectEpeople: A Social Media Coproduction Research Study

Abstract: BackgroundUsing social media for research purposes is novel and challenging in terms of recruitment, participant knowledge about the research process, and ethical issues. This paper provides insight into the recruitment of European parents of children with specific congenital anomalies to engage in coproduction research by using social media. Secret Facebook groups, providing optimal security, were set up for newly recruited research-aware parents (RAPs) to communicate privately and confidentially with each ot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 15 publications
(16 reference statements)
1
24
0
Order By: Relevance
“…As previously reported [ 1 ], in the coproduction research stage, 32 research aware parents (RAPs) were recruited from 9 European countries via their parent support organization (n=18), CA registry leader (RL; n=7), ConnectEpeople project survey (n=5), and the project public Facebook page (n=1) and by word of mouth (n=1). On average, parents had two discussions with the researcher before agreeing to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported [ 1 ], in the coproduction research stage, 32 research aware parents (RAPs) were recruited from 9 European countries via their parent support organization (n=18), CA registry leader (RL; n=7), ConnectEpeople project survey (n=5), and the project public Facebook page (n=1) and by word of mouth (n=1). On average, parents had two discussions with the researcher before agreeing to participate.…”
Section: Methodsmentioning
confidence: 99%
“…This is the second paper from the ConnectEpeople project. The first paper reported on project recruitment and findings from coproduction research [ 1 ]. This second paper sets out to share the overall learning from the research, technical and ethical obstacles, challenges, and successes in developing the ConnectEpeople e-forum.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of SM by patients with rare diseases show that they seek out online groups for information, social support, and advice. 4,6-11 A 2020 study by Çinar et al found patients and families affected by OFCs share similar motivations for using SM support groups. 4 Two studies in 2018 identified learning about new research as an impetus for participation in OFC SM groups.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional barriers, such as conflicting work and study center schedules or travel time, are not issues with SM-based recruitment, which allows patients to complete study surveys or sample collections on their own time in the privacy of their home. 6,11-21 In addition, studies that recruit via Facebook and other SM sites are consistently geographically diverse and typically demographically representative of the larger patient population. 17,21 Those studies that are not demographically representative tend to be overly white and female.…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant literature on coproduction, focusing inter alia on conceptual models [ 1 , 2 , 8 ], enhancing the quality care of children with cystic fibrosis [ 9 ], coproduction in the design of oral health care services for older people [ 10 ], using coproduction to involve parents in defining research priorities on congenital anomalies [ 11 ], and the possibilities and challenges of co-production in health system-wide reforms [ 12 ]. More recently, Palmer has advocated for ‘a science of participation’, given the scholarly focus on coproduction [ 13 ].…”
Section: Introductionmentioning
confidence: 99%